THE EFFECTIVENESS OF THE RIGHT TO EDUCATION IN BRAZIL: EJA AS AN INSTRUMENT THAT CONSIDERS THE SOCIAL AND EDUCATIONAL PATH OF SUBJECTS - Suave, Angela Michele; Bussolotti, Juliana Marcondes [UNESP]; Santos, Tiago Bueno dos; Gomes, Felipe Adriano (Fundacao Univ Tocantins, 2021)
This article deals with the theme of the construction of Youth and Adult Education (EJA) in Brazil from the historical and pedagogical process, considering the multidimensionality of its trajectory. The reflections unfolded in order to define this concept in the city space and, finally, reflect on the dimensionality and horizons of EJA. This analysis proposal was developed from the bibliographic research methodology to make a study with the historical-critical approach, which seeks, from the study of the historical process, to analyze and reflect on the development of educational dynamics in Brazil aimed at young people and adults. In this sense, it is expected to contribute to the deepening of issues related to the education of young people and adults in conceptual and historical terms, dialoguing and establishing relationships with other forms of perception of this process.
Keywords: EJA; Social Inclusion; Social Rights